2022
DOI: 10.3389/fendo.2022.871380
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Parathyroid Hormone and Zoledronate Acid on Prevention Particle Wears-Induced Implant Loosening by Promoting Periprosthetic Bone Architecture and Strength in an Ovariectomized Rat Model

Abstract: Implant-generated particle wears are considered as the major cause for the induction of implant loosening, which is more susceptible to patients with osteoporosis. Monotherapy with parathyroid hormone (PTH) or zoledronate acid (ZOL) has been proven efficient for preventing early-stage periprosthetic osteolysis, while the combination therapy with PTH and ZOL has exerted beneficial effects on the treatment of posterior lumbar vertebral fusion and disuse osteopenia. However, PTH and ZOL still have not been licens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“… 338 Moreover, Ti particles inhibit the osteogenic differentiation of osteoblasts via the BMP/SMAD signaling pathway. 339 Furthermore, we found that titanium particles lead to an aberrant increase in GSK‐3β activity, which inhibits the Hh/Gli1 signaling pathway, ultimately leading to an inhibition of the osteogenic process. 7 Furthermore, we demonstrated that up‐regulation of SIRT3 expression enhanced the osteogenic differentiation of PPO289 by decreasing NLRP3 inflammasome expression via the GSK‐3β/β‐catenin signaling pathway.…”
Section: The Role Of Bone Homeostasis In Skeletal Diseasementioning
confidence: 88%
“… 338 Moreover, Ti particles inhibit the osteogenic differentiation of osteoblasts via the BMP/SMAD signaling pathway. 339 Furthermore, we found that titanium particles lead to an aberrant increase in GSK‐3β activity, which inhibits the Hh/Gli1 signaling pathway, ultimately leading to an inhibition of the osteogenic process. 7 Furthermore, we demonstrated that up‐regulation of SIRT3 expression enhanced the osteogenic differentiation of PPO289 by decreasing NLRP3 inflammasome expression via the GSK‐3β/β‐catenin signaling pathway.…”
Section: The Role Of Bone Homeostasis In Skeletal Diseasementioning
confidence: 88%
“…PTH 1-34 interacts with PTH1R on the surface of osteoblasts and osteocytes and contributes to expanding the number of osteoblasts by reducing apoptosis and exerting an anabolic effect on bone ( Silva and Bilezikian, 2015 ; Chen et al, 2021 ). Previous studies have used PTH in combination with bisphosphonates to achieve better osteogenesis and reduce the amount of PTH in the treatment of osteoporosis ( Zhang and Song, 2020 ; Zhou et al, 2022 ). However, one risk of bisphosphonates is medication-related osteonecrosis of the jaw ( Pires et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…After administered teriparatide for 12 weeks, new bone formation was found around external and internal surfaces of titanium implants in osteoporotic rabbits [ 6 ]. And following teriparatide treatment, osteoporotic SD rats also showed an increased value of maximal pull-out force as a sign of increased implant fixation [ 7 ]. Similarly, Li et al‘s investigation further showed how teriparatide treatment altered the peri-implant bone mass and density associated to an increase in implant fixation in osteoporotic rats by micro-CT and histological results [ 8 ].…”
Section: Introductionmentioning
confidence: 99%